Co-Education and Gender:The End of the Experiment? - Clark, Ian (Education Policy Analysis Archives, 2004)
This article has two inseparable aims: (a) to analyse the relative merits of single-sex and co-educational constructs on self-concept, academic performance and academic engagement; (b) to investigate the manner in which each type of schooling interacts with the individual student; student “peers,” close family, and teachers.